Design Of A Control System For A Reconfigurable Conveyor System Using PLC - Lim, Victor Abraham Su Kang (2019)
Reconfigurable is used by a manufacturing system to emphasize the importance of being able to change and improve the functionality of the system. This report presents the work done on the control system of the Reconfigurable Conveyor System (RCS) using Programmable Logic Controller (PLC). Due to the customer demand in a variety of products, a manufacturer needs to find alternatives to provide flexibility and reconfigurability to the manufacturing system. Design for reconfigurability is essential in manufacturing because customer demand in product variety is increasing. Thus a control system becomes the main role in the reconfiguration of manufacturing systems. The flexibility of the system will determine the system performance in the manufacturing industry. The objective of this project is to design the control system using a Petri Net (PN) model and generates Ladder diagram (LD) PLC. PLC system becomes essential in the reconfigurability to control the operation through the cx-programmer software. The programming software generates a different modification method to determine the changeability. The PLC is used for the communication between the cx-programmer software and RCS by using Local Area Network (LAN) cables. The integration between PLC and RCS established by using the Function Block (FB) instruction to enables the data transfer and exchanging data. Therefore this project used PLC to design the control system that capable of supporting the changeability and quick reconfiguration of the RCS. The design control system in RCS enables the control system to be flexible and effective to performed multiply of tasks. It is hoped that this project able to give a beneficial for efficient material system.